2018
DOI: 10.3390/f9030104
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Microhabitat Frequency and Diversity in Mixed Mountain Forests in South-Western Germany

Abstract: Tree-related microhabitats are an important determinant of forest biodiversity. Habitat trees, which typically provide many microhabitats such as hollows, crown dead wood, etc., are therefore selected to maintain those structural attributes within managed forests. To what extent the occurrence of microhabitats on potential habitat trees may be predicted from common tree attributes is a question of high practical relevance. Until now, most studies have attempted to predict the quantity of microhabitats at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…woodpecker feeding holes or bark characteristics). Previous studies comparing microhabitat number between living and dead trees almost all found higher microhabitats numbers on dead trees (see [17]). However, this difference varied across studies, from 1.2x more microhabitats in Mediterranean forest [15], 2x more in five forests in France [12], to 4x more on habitat trees in south-western Germany [31].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…woodpecker feeding holes or bark characteristics). Previous studies comparing microhabitat number between living and dead trees almost all found higher microhabitats numbers on dead trees (see [17]). However, this difference varied across studies, from 1.2x more microhabitats in Mediterranean forest [15], 2x more in five forests in France [12], to 4x more on habitat trees in south-western Germany [31].…”
Section: Discussionmentioning
confidence: 95%
“…Finally, our models assumed – unrealistically – microhabitat number to increase exponentially with diameter. Recent studies [17], as well as ecological theory (e.g. species-area relationship), tend to rather show a saturated (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature suggests the large trees act as keystone habitat features (DeMars, Rosenberg, & Fontaine, 2010). The rough, corrugated bark, and multiple microhabitats, like small places of rot, of larger trees host insects, providing rich and abundant forage for birds of multiple guilds (Großmann, Schultze, Bauhus, & Pyttel, 2018;Kozák et al, 2018;Larrieu & Cabanettes, 2012). Studies have tied specifically bark-foraging bird species to large-diameter trees (Pennington & Blair, 2011;Whelan & Maina, 2005).…”
Section: Legacy Stand Structurementioning
confidence: 99%